ICCREM 2018 : Analysis of Real Estate and the Construction Industry - Wang, Yaowu; Zhu, Yimin; Shen, Geoffrey Q. P.; Al-Hussein, Mohamed (American Society of Civil Engineers, 2018)
Selected papers from the International Conference on Construction and Real Estate Management 2018, held in Charleston, South Carolina, August 9-10, 2018. Sponsored by the Modernization of Management Committee of the China Construction Industry Association and the Construction Institute of ASCE. This collection contains 34 peer-reviewed papers on real estate and the construction industry. Topics include: real estate finance and economics; urban residential development; demographics and housing demand; and real estate inventory and the economy. These papers will be of interest to construction professionals, researchers, planners, contractors, and banking and government officials.
Keywords: Real estate business.; Housing -- China.; Construction industry.; elektronické knihy; electronic books